2019
DOI: 10.1039/c9cy01997a
|View full text |Cite
|
Sign up to set email alerts
|

Fast screening of homogeneous catalysis mechanisms using graph-driven searches and approximate quantum chemistry

Abstract: Automatic analysis of competing mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 48 publications
(64 reference statements)
0
35
0
Order By: Relevance
“…31 We have also shown that when combined with semiempirical or ab initio electronic structure calculations, our GDS scheme can correctly identify the accepted "correct" mechanism of catalysis by an organometallic complex. 38 These same successful calculations have also highlighted two important algorithmic issues in our GDS approach. First, our approach currently does not account for permutational invariance among reactive atoms and molecules when searching for reaction mechanisms.…”
Section: Introductionmentioning
confidence: 72%
“…31 We have also shown that when combined with semiempirical or ab initio electronic structure calculations, our GDS scheme can correctly identify the accepted "correct" mechanism of catalysis by an organometallic complex. 38 These same successful calculations have also highlighted two important algorithmic issues in our GDS approach. First, our approach currently does not account for permutational invariance among reactive atoms and molecules when searching for reaction mechanisms.…”
Section: Introductionmentioning
confidence: 72%
“…The method also benefits from working in graph space, where reactions are simply graph transformations. This has been shown to be a practical way to explore reactive events by Habershon and co‐workers 26,27,97–100 …”
Section: Methodsmentioning
confidence: 99%
“…This has been shown to be a practical way to explore reactive events by Habershon and co-workers. 26,27,[97][98][99][100] The workflow of ChemKnow is detailed as follows:…”
Section: Chemical Knowledge (Chemknow)mentioning
confidence: 99%
“…Most relevant to our work, we anticipate that this algorithm may be of particular utility in the context of automated, high‐throughput schemes to attempt de novo design of potential molecular catalysts 17,19,20,24,26,30–35 . As well as preconditioning the position and orientation of molecules, deciding whether the product and reactant molecules require conformational intermediates and providing reasonable guesses (prior to PES evaluations) of these would be a natural next step to implement, and for which work is currently underway.…”
Section: Discussionmentioning
confidence: 99%